1995
DOI: 10.3354/meps127235
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation and the eutrophication of coastal lagoons

Abstract: An ecosystem-level experiment was conducted to identify the nutrient most limiting to productivity and biomass in the marine lagoons of the northeast United States. Mesocosms containing a complex of species characteristic of shallow coastal marine environments were enriched with P alone, N alone, or combined N plus P, at loadings typical of highly enriched natural lagoons. The mesocosms showed significant responses to ennchment with N alone but not P alone, indicating limitation by N. Enrichment with N alone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 19 publications
3
77
0
3
Order By: Relevance
“…Research has shown that nutrient limitation in lagoons is a complex matter; in particular nitrogen limitation is important (Nixon 1982;Taylor et al 1995). During the summer and spring, raw nutrients are more important in Gialova, reflecting the growth stage of meiofaunal food (bacteria, microphytoplankton) and perhaps limiting distribution and density.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that nutrient limitation in lagoons is a complex matter; in particular nitrogen limitation is important (Nixon 1982;Taylor et al 1995). During the summer and spring, raw nutrients are more important in Gialova, reflecting the growth stage of meiofaunal food (bacteria, microphytoplankton) and perhaps limiting distribution and density.…”
Section: Discussionmentioning
confidence: 99%
“…Some systems have shown a phytoplankton dominated-response (Taylor et al, 1995) while others presented macroalgal dominance (Lavery and McComb, 1991;Valiela et al, 1992). Shallow coastal estuaries with low nutrient availability in the water are more likely to be dominated by benthic algae and vascular plants due to the potential of these species to sequester nutrients from the sediments (Sand-Jensen and Borum, 1991;Havens et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In estuarine systems, plant communities are constituted by complex assemblages of phytobenthos and phytoplankton, each with different access to nutrients and light (Taylor et al, 1995) that can constitute potentially limiting factors to the primary production of these aquatic autotrophs (Pedersen and Borum, 1992). Phytoplankton and fast-growing ephemeral macroalgae are often limited by nutrient availability, while slow-growing perennial macroalgae and rooted macrophytes seem less dependent on nutrient concentrations (Sand-Jensen and Borum, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Duarte (I 995), Taylor et al (1995), and others have suggested that in waters where nutrient supply increases, seagrasses are replaced by macroalgae, which in turn can be replaced by phytoplankton as the dominant producers. Here we use data from different estuaries of Waqlloit Bay to put together a quantitative de- piction of how seagrasses might be replaced by macroalgae and phytoplankton as the dominant producers, under the influence of progressive nitrogen enrichment (Fig.…”
mentioning
confidence: 99%